Penatalaksanaan Keperawatan Tentang Pencegahan Obesitas pada Anak Usia Sekolah - Nessa Ishmah Munyati (2021)
Obesity in children is a complex health problem with many underlying factors. The incidence of overweight and obesity in childhood has been recognized as a serious problem in the world experienced by children and adolescents over the last three decades (Shanon et.al, 2017). Behavioral factors include the consumption of high-calorie sugary foods and drinks that contain low nutritional value, which are available to children. Lack of physical activity also contributes to obesity where children spend a lot of time using technology such as cell phones, television, computers or video games. In addition, environmental factors, home, school, and community environment all play an important role in the development and maintenance of a child's healthy diet and involvement in physical activity (Hill Jo in Xu, 2015). Good education and demonstrations need to be given to parents and schools in achieving optimal health in preventing obesity in school-age children and this is one of the roles of community nurses as educators. So, the researcher created a scientific work product in the form of a booklet entitled "Nursing Management About Prevention of Obesity in School Age Children" with material that explains the importance of managing a healthy lifestyle, how to prevent obesity